Integrity and ethics and its effect on employees in organization - Adeline, Jol. (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Integrity and ethics are elements that always stay with organizational context worlwide yet, their effects on employee in organization have not been thoroughly investigated. The purpose of this case study is to study integrity and ethics and its effect on employees in organization. This study was done in one organization, a secondary school involving 10 teachers who were judgmentally sampled from a population of 80 teachers. Data were gathered using open-ended questionnaire survey. This research finding reveals that integrity and ethics does give significant effect on employees in organization in terms of workplace surrounding and during performing task. Furthermore, the results discover arise of some appealing problems that hinder practice of integrity and ethics. Therefore, possible solution to counter-attack integrity and ethics problem must be done in more effective ways.